MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DENGAN PENGGUNAAN LAYANAN BIMBINGAN KELOMPOK - Sarbini, Sarbini (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The purpose of this study was to find out whether learning motivation in Mathematics subjects could be improved by the use of group guidance services for class X students at Rimau Island 1 High School. The problem in this study was students' low mathematics learning motivation. The problem of this study is whether the motivation to learn on Mathematics subjects can be improved by using group guidance services for class X students at Rimau Island 1 High School. The method used in this study was the pre-experimental method with the design of one group pretest-posttest, and analyzed by non-parametric statistics using the Wilcoxon test. The research subjects were 8 students who had low motivation to learn Mathematics. The results obtained in the study showed that motivation to learn Mathematics had a significant increase after the provision of group guidance services. This is indicated by the results of the pretest and posttest which obtained zcount = -2.521 and ztable 0.05 = 4. Because zcount <ztable then, Ho is rejected and Ha is accepted, meaning there is a significant difference with the level of 5% between the motivation to learn Mathematics before being treated and after being given treatment with group guidance services to the research subjects. Conclusions in this study motivation to learn Mathematics can be improved using group guidance services. Suggestions given to students should take group guidance services if they experience difficulties in increasing motivation to learn Mathematics. Suggestions for guidance and counseling teachers should be able to help students increase motivation to learn Mathematics through the use of guidance and group services and subsequent researchers.